The Silk Vista Baby – The UK experience. Issue 2 (April 2022) - Bhogal, P; Makalanda, HLD; Wong, K; Keston, P; Downer, J; Du Plessis, JC; Nania, A; Simonato, D; Fuschi, M; Chong, W; O'Reilly, S; Rennie, I
Background: The Silk Vista Baby (SVB) flow diverter (FDS) is the only FDS deliverable via a 0.017 inch microcatheter and is specifically designed for the distal vasculature. We sought to evaluate the safety and efficacy of the SVB. Materials and Methods: We performed a retrospective review to identify SVB cases at 4 tertiary neurosurgical centres within the U.K. Clinical, procedural, angiographic and follow-up data were collected. Results: We identified 60 patients (35 female, 58%) of average age 54 ± 10.5 (range 30–72) with 61 aneurysms, 50 (81.9%) located in the anterior circulation. The majority of the aneurysms treated were unruptured (46, 75.4%) and saccular (46, 75.4%). Dome size was 6.2 ± 6.2 mm (range 1–36mm) and parent vessel diameter was 2.3 ± 0.4 mm (range 1.2-3.3 mm). An average number of 1.07 devices were implanted. Coils or other devices were implanted in 14 aneurysms (23.3%). At last angiographic follow-up (n = 55), 7.5 ± 4.2 months post-procedure, 32 aneurysms (57.1%) were graded as RRC I, 7 (12.5%) RRC II, and 17 RRC III (30.4%). Clinical complications, excluding death, were seen in 4 patients (6.8%) including 1 delayed aneurysm rupture and 3 symptomatic ischaemic events. Only one patient had permanent morbidity (mRS 1). 3 patients died during follow-up (5.1%); 2 deaths were related to the aneurysms (3.4%) – one ruptured dissecting MCA aneurysm, and one giant partially thrombosed posterior circulation aneurysm. 93% of patients were mRS ≤ 2 at last follow-up. Conclusion: The SVB has high rates of technical success and an acceptable safety profile. Distal aneurysms may occlude slower due to relative oversizing of the devices.